'Fear of missing out': antecedents and influence on purchase likelihood. Issue 3 (2nd July 2020) - Good, Megan C.; Hyman, Michael R.
ABSTRACT: 'Fear of missing out' (FOMO) is a recent but widely recognized phenomenon. Some emotional antecedents of FOMO, such as anticipated elation and anticipated envy from other people, can boost FOMO. Other emotional antecedents, such as comforting rationalizations, can decrease FOMO. Because FOMO can influence consumers' experience-related attitudes and behaviors meaningfully, it behooves marketing scholars and practitioners to understand FOMO and the potential of FOMO-laden appeals to increase sales. Although social scientists generally treat FOMO as a personality trait, FOMO-laden appeals that extol the future experiences of close friends or family members can induce a FOMO spike.